Control of Brucella melitensis in endemic settings: A simulation study in the Nile Delta, Egypt. Issue 4 (17th November 2020) - Hegazy, Yamen Mohammed; Schley, David; Ridler, Anne; Beauvais, Wendy; Musallam, Imadidden; Guitian, Javier
Abstract: Small ruminant brucellosis remains endemic in many low‐ and middle‐income countries (LMICs), where it poses a major economic and public health burden. Lack of resources to support long‐term vaccination, inherent characteristics of small ruminant production systems such as mixing of different flocks for grazing and limitations of the vaccines currently available, which can induce abortion in pregnant animals, have all hindered the effectiveness of control programmes. In the current study, the likely effect of different control scenarios on the seroprevalence of brucellosis among the small ruminant population in a hypothetical area of an endemic region was simulated using compartmental models. The model accounts for variability in transmission rates between villages and also simulates control scenarios that target villages with high seroprevalence. Our results show that vaccination of young replacement animals only can effectively reduce the prevalence of small ruminant brucellosis in endemic settings if a high vaccination coverage is achieved. On the other hand, test‐and‐slaughter alone is not a promising strategy for control of small ruminant brucellosis under husbandry practices typical of endemic low‐resource settings. Furthermore, results show the potential success of some strategies requiring a relatively low overall vaccination coverage such as the vaccination of 50% of young replacements and 25% of adult animals each year. Control strategies selectively targeting high initial seroprevalence villages ( p  > 10%) did not decrease the overall seroprevalence to acceptable levels in most of the examined scenarios. Scenario analysis showed that the efficacy of the simulated control strategies can be improved mostly by decreasing the proportion of between‐village trade and also by improving the performance of the used serological tests and increasing vaccine efficacy.